2018
DOI: 10.1002/jum.14691
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Ultrasound Appearance of the Normal Parathyroid Using an Intraoperative Procedure

Abstract: The normal parathyroid had hyperechoic echogenicity on both intraoperative and percutaneous US imaging. Residual tissue of parathyroid glands can also be observed in some parathyroid abnormalities with an echogenic appearance on US imaging and confirmed by histopathologic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
(31 reference statements)
2
14
0
Order By: Relevance
“…1). Only a few scholars have reported this manifestation of US previously [18].The sensitivity of this sign in the diagnosis of parathyroid nodules is 63.6%, and it is highly sensitive to parathyroid adenomas with a maximum diameter of ≤ 1.55 cm. However, it is difficult to Fig.…”
Section: Discussionmentioning
confidence: 98%
“…1). Only a few scholars have reported this manifestation of US previously [18].The sensitivity of this sign in the diagnosis of parathyroid nodules is 63.6%, and it is highly sensitive to parathyroid adenomas with a maximum diameter of ≤ 1.55 cm. However, it is difficult to Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Previous work suggested normal parathyroid glands may be hyperechoic and homogeneous on ultrasound, although gland identity was never confirmed by histopathological, biochemical, or fluorescence review. 12 Multiple other studies have concluded ultrasonography to be unreliable for identification of normal parathyroid glands. 3 , 13…”
Section: Discussionmentioning
confidence: 99%
“…11 Previous work suggested normal parathyroid glands may be hyperechoic and homogeneous on ultrasound, although gland identity was never confirmed by histopathological, biochemical, or fluorescence review. 12 Multiple other studies have concluded ultrasonography to be unreliable for identification of normal parathyroid glands. 3,13 Here, however, we report successful identification of normal parathyroid glands using ultrasound, in which they appear as distinct, homogeneously hyperechoic structures in the perithyroidal central neck.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few scholars have reported this manifestation of US. [15]The sensitivity of this sign in the diagnosis of parathyroid nodules is 63.6%, and it is highly sensitive to parathyroid adenomas with a maximum diameter of ≤ 1.55 cm. However, it is di cult to nd residual normal glands when the tumor is large, which may be caused by smaller residual normal gland tissue and compression.…”
Section: Discussionmentioning
confidence: 99%